Atomically thin mononitrides SiN and GeN: New two-dimensional wide band gap semiconductors. (27th June 2018) - Qian, Yan; Du, Zhengwei; Zhu, Renzhu; Wu, Haiping; Kan, Erjun; Deng, Kaiming
Abstract: To match well with the Si-based electronics and satisfy the demand of miniaturization in modern industry, low-dimensional Si-based semiconductors maybe are the best candidates. Owing to the lack of such materials, in this work, we predicted two-dimensional atomically thin mononitrides SiN and GeN via a swarm structure search method and density functional theory. By the employment of HSE functional, both SiN and GeN are calculated as indirect wide band gap semiconductors with the gaps of and, respectively. Ab initio molecular-dynamics calculation displays that both mononitrides can exist stably even at an extremely high temperature of . Notably, phonon limited electron mobilities are evaluated as and for SiN and GeN, respectively. We hope this work could expand the family of low-dimensional Si-based and wide band gap semiconductors.